Validitas Lembar Kerja Peserta Didik (LKPD) Berbasis Inkuiri Untuk Melatihkan Literasi Sains Peserta Didik SMA Pada Materi Perubahan Iklim - Agustin, Zulfani Nurdiana; Sanjaya, I Gusti Made (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2024)
This study aims to describe the validity of inquiry-based LKPD to train science literacy of high school students on climate change material. This research uses a type of development / Research and Development (R&D) with a 4D model (Define, Design, Develop, Disseminate). When the define stage begins by analyzing the initial problem by means of literature study. Next is the design at this stage is the process of preparing learning tools developed in the form of Student Worksheets (LKPD). At the development stage, it is to conduct a validation test of the LKPD learning tool to expert validators and a trial to students. The dissemination stage is not carried out, only until it is carried out by disseminating the research results in the form of scientific articles containing research on the development of published learning tools. The validity of the worksheet was assessed with 13 aspects on the validator assessment sheet. Based on the assessment aspects carried out by 2 expert validators, it was found that the validity of the LKPD developed obtained a validity of 0.87, reliability of 0.87, and homogeneity of 0.96. The results of the validation show that the LKPD developed is declared valid and reliable, so it is suitable for use in learning activities to improve students' science literacy on climate change material.